Effect of cooling rate following β forging on texture evolution and variant selection during β → α transformation in Ti-55511 alloy. (20th June 2022) - Dong, Yue; Liu, Xingang; Zou, Junjie; Ke, Yujiao; Liu, Pengwei; Ma, Lan; Luo, Hengjun
Highlights: α-precipitation in an interface instability manner has an inhibitory effect on the growth of βSRX grains from 0.1 to 0.05 °C/s. α follows BOR relationship with the side of adjacent β grains having the same or similar {110} or {111}. α-phase is preferentially precipitated at β-medium angle GBs between 30 and 45 °, and most of α phases rotate 50–60 ° / <-12–10>. The texture type transforms gradually from RGoss {110} <1–10> to Brass {110} <1–12> from 25 °C/s to 1 °C/s. The intensity of cubic texture and α-fiber texture is gradually weakened due to the change of α texture types, but still retained from 25 to 0.05 °C/s. Abstract: The control of the post-forging cooling rate has been a key issue in the industrial production process of titanium alloys. We investigated texture evolution and variant selection (VS) during β → α transformation through high-temperature compression experiments followed by quantitative control of varying cooling rates. Results show that post-forging cooling rates affect β grains, α variants, and α / β textures. The α precipitation inhibits motions of β static recrystallization (βSRX ) grain boundaries and thus leads to grain refining from 0.1 °C/s to 0.05 °C/s. Further analysis reveals that lamellae grain boundary widmanstatten α (αWGB ) keeps growing rapidly within β-grain in an interface instability manner at 0.1–0.05 °C/s. Most of α-phase with 50°–60°/<-12–10> is preferentially precipitated at β-medium angle GBs between 30° and 45° and strictly follows BOR with the side of of adjacent β-grain with the same or similar {110} or {111}. Moreover, the texture type transforms gradually from RGoss {110} <1–10> to Brass {110} <1–12> from 25 °C/s to 1 °C/s. βSRX grains exhibit (102) [-201] texture, while the corresponding α has textures of <0001>//Z and <11–20>//Y from 1 °C/s to 0.05 °C/s. Our findings lay a profound theoretical foundation in microstructure evolution of near-β titanium alloy for industrial production. Graphical abstract: Image, graphical abstract .